Evaluation of the Physical and Mechanical Properties of Handmade Paints with Inorganic Pigments from Cusco According to American Society for Testing and Materials’ Standards for Architectural Applications - Carlos Guillermo Vargas Febres; Ana Torres Barchino; Juan Serra Lluch; Edwin Roberto Gudiel Rodríguez (Architecture)
The artisanal production of paints using inorganic pigments from the Cusco Valley is considered a sustainable alternative to the use of synthetic industrial paints. This approach not only helps reduce the environmental footprint associated with the use of volatile organic compounds (VOCs) but also utilizes local materials. The present study evaluates the physical and mechanical properties of paints obtained from natural pigments through standardized tests based on the American ASTM standards, focusing on adhesion (ASTM D-3359), drying time (ASTM D-1640), surface hardness (ASTM D-3363), and the performance of the paints when exposed to the environmental factors of Cusco (under real conditions). In this regard, the pigments were extracted from traditional quarries and processed through the sedimentation method (MS) and ball milling (MG). The produced paints were formulated with the addition of polyvinyl acetate (PVA) as a binder and water as a solvent and were applied to standardized panels. The results show that all samples meet the requirements of the technical parameters, demonstrating good adhesion, appropriate drying times, and acceptable hardness for architectural coatings, Chromatic variations (ΔE*) were recorded depending on the processing method and the level of environmental exposure, with paints containing ground pigments (MG) being more resistant to fading. This study concludes that these artisanal formulations represent a technically viable and culturally relevant alternative to industrial coatings, especially in contexts of heritage restoration or sustainable architecture.